Revisiting Religious Environmentalism in Indonesia: Navigating Ethics, Politics, and Policy - Testriono Testriono; Savran Billahi (Studia Islamika, 2025)
This special issue revisits the study of religious environmentalism in Indonesia by bringing together essays that both engage with and critically examine Islam as an active, lived force in environmental activism. Collectively, the contributions open new pathways in the study of religion and the environment by demonstrating that the integration of Islam into environmental conservation is not frictionless. The essays make a substantive contribution to strengthening the methodological foundations of Islam and environmental studies through a rigorous multidisciplinary approach, marking a clear shift from predominantly theological justification toward empirically grounded analyses that combine field-based evidence with sensitivity to religious values. Beyond portraying the current state of the field, this special issue advances a more demanding, empirically grounded, theoretically informed, methodologically robust, and analytically rigorous research agenda for future scholarship.